The Evolution of Hemophilia Pharmacological Treatments and Therapeutic Targets at the Turn of the Third Millennium - Coppola, Antonio; Zani, Matteo; Quintavalle, Gabriele; Focosi, Daniele; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2024)
Historically, the aim of treatment for hemophilia, the congenital X-linked hemorrhagic disorder due to deficiencies of coagulation Factor (F) VIII (hemophilia A) or FIX (hemophilia B), has been the replacement through factor concentrates, whose regular administration (i.e., prophylaxis) has been shown to be highly effective in preventing bleeding complications and it is currently considered the gold standard of hemophilia treatment. However, continuous technological progress (i.e., plasma-derived factor concentrates, recombinant standard and extended half-life [EHL] products) has allowed clinicians operating at hemophilia treatment centers to individualize the management of persons with hemophilia, improving outcomes, adherence to therapy, and their quality of life. The achievement of normal hemostasis, the final goal that now seems possible with new-generation EHL products, non-replacement and gene therapies, will translate into normalization of life for persons with hemophilia, also addressing health equity (i.e., rendering them indistinguishable from their healthy peers). The evolution of hemophilia treatment and, in parallel, of therapeutic targets in the management of hemophilia patients over the last decades will be critically discussed in this narrative review.
Keywords: factor concentrates; health equity; hemophilia; management; non-replacement treatment; prophylaxis